ANALISIS KONDUSIFITAS KELEMBAGAAN DAN SOSIO-KULTURAL MASYARAKAT BAGI PENGEMBANGAN EKONOMI WILAYAH SEKITAR JEMBATAN SURAMADU SISI MADURA - Bondan Satriawan (Trunojoyo University of Madura, 2010)
This study tries to picture the conducivesness of the region around Suramadu Bridge of the Madura side that consist of 8 vilages. The main focus of the study is to see how far the institutional and sosio-cultural condition of the surrounding society supports the further potency of development in that region. By doing so the study uses Likert scale to quantify the magnitude of the support for further economic development for the region. This study surveys 320 respondens from those 8 vilages purposively. The result of the study shows that in general there is no problem with institutional and sosio-cultural of the related region to support the further economic development of the region.